2016
DOI: 10.5005/jp-journals-10028-1202
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatoid Adenocarcinoma of the Lung

Abstract: Hepatoid adenocarcinoma lung (HAL) is an extremely rare type of extrahepatic adenocarcinoma with morphological similarity to hepatocellular carcinoma. We report a case of 59 years male smoker who presented with anorexia, weight loss and cough. Chest X-ray revealed a homogenous opacity in the left upper and mid zone. Computed tomography (CT) chest showed a left upper lobe mass with enlarged hilar lymph nodes. Serum alpha fetoprotein (AFP) was normal. Guided fine needle aspi ration cytology (FNAC) of the mass re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13] Grossman et al reviewed 28 cases of HAC lung reported in the English literature, between January 1980 and June 2015. [5] Additional six case reports have been published from June 2015 to December 2018 including one Indian case report by Vellaisamy et al [3] In these reported 34 cases of primary HAC lung, 33 were males with age ranging from 36 to 77 years (mean 57 years). History of chronic smoking was significant in 19 cases, suggesting that this neoplasm is common in middle to old age men and chronic smoking can be a predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13] Grossman et al reviewed 28 cases of HAC lung reported in the English literature, between January 1980 and June 2015. [5] Additional six case reports have been published from June 2015 to December 2018 including one Indian case report by Vellaisamy et al [3] In these reported 34 cases of primary HAC lung, 33 were males with age ranging from 36 to 77 years (mean 57 years). History of chronic smoking was significant in 19 cases, suggesting that this neoplasm is common in middle to old age men and chronic smoking can be a predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
“…[2] There are only 34 cases of primary HAC of the lung origin that are described in the world literature, of which only one case has been reported from India. [3] In our study, we report two cases of primary HAC of the lung in two male patients which was diagnosed on fine-needle aspiration cytology (FNAC) with ancillary studies. The present study, to best of our knowledge, is the second to report with the comprehensive clinicopathological data of two cases of primary HAC of the lung in the Indian literature.…”
Section: Introductionmentioning
confidence: 98%